Appreciative inquiry and the co-creation of an evaluation framework for Extension for Community Healthcare Outcomes (ECHO) implementation: a two-country experience. (June 2022) - Ghosh, Smita; Struminger, Bruce B.; Singla, Neeta; Roth, Brenna M.; Kumar, Anil; Anand, Sunil; Mtete, Emmanuel; Lusekelo, Jacob; Massawe, Irene; Jarpe-Ratner, Elizabeth; Seweryn, Steven M.; Risley, Kris; et al.
Abstract: Persistent gaps exist in healthcare workers' capacity to address HIV and tuberculosis in Asia and Africa due to constraints in resources and knowledge. Project ECHO (Extension for Community Healthcare Outcomes) leverages video-enabled technology to build workforce capacity and promote collaboration through mentorship and case-based learning. To understand current perceptions of ECHO participants and develop a comprehensive evaluation framework for ECHO implementation, we utilized modified appreciative inquiry guided focus group discussions (FGD) in India and Tanzania and called it SCORE (Strengths, Challenges, Opportunities, Results, and Evaluation). Content and thematic analysis of transcripts from FGDs and key-informant interviews triangulated perceptions of diverse stakeholders about ECHO implementation and identified key elements for development of the framework. The perceived strengths (S) were capacity building and establishing communities of practice. The perceived challenges (C) included securing resources, engaging leadership, and building systems for monitoring impact. Improved internet connectivity, addressing logistical challenges, encouraging session interactivity, and having strategic scale-up plans were perceived opportunities (O). Additionally, gathering measurable results (R) led to development of a comprehensive evaluation (E) framework. Contextualizing and facilitating SCORE with qualitative analysis of findings 6–12 months post-ECHO implementation may serve as a best practice to assess mid-course corrections to improve ECHO implementation quality. Highlights: Modified appreciative inquiry method – SCORE. SCORE: Strengths, Challenges, Opportunities, Results, Evaluation. SCORE facilitated the gathering of perceptions about implementing Extension for Community Healthcare Outcomes (ECHO) programs. Local contextualization of SCORE was acceptable and feasible in India and Tanzania. SCORE facilitated the co-creation of a comprehensive evaluation toolkit.